The RMB's global role as an anchor currency: No evidence - Kari Heimonen; Risto Rönkkö (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
This study examines the role of the Chinese renminbi (RMB) as an international anchor currency. After China abandoned its tight US dollar (USD) peg in 2005, the RMB found greater popularity as a reserve currency. This change in the RMB's role reflected China's growing presence in the global economy, even challenging the USD in some of the 155 countries that signed on to the Belt and Road initiative (BRI). Modifying the approach of Ahmed (2021) to estimate basket weights in exchange rate policy for the currencies of 63 advanced and emerging economy currencies, we account for potential drivers of the exchange rate omitted in previous studies to obtain unbiased anchor weight estimates. Unlike earlier studies, we find that the RMB's anchor weight in exchange rate policies remains low irrespective of China's global role. Overall, the weight of the RMB averaged 6 %, compared to an average share of 58 % for the USD and 35 % for the euro. We also find that the USD, euro and yen anchor choices are strongly interlinked. A change in the anchor weight of any of these three currencies results in a strong opposite change in the weights of other two. Changes in RMB anchoring, however, do not materially impact USD, euro and yen weights. An increase in financial markets volatility leads developing countries to increase anchor weights of the developed countries currencies USD, euro and yen. Heightened geopolitical uncertainty only increases the weights of the USD and euro.
urn:nbn:fi-fe2024042321049
Keywords: F31; F33; 330; exchange rate; currency peg; RMB